Bovine Genital Leptospirosis: An Update of This Important Reproductive Disease - Luiza Aymée; Julia Mendes; Walter Lilenbaum (Animals, 2024)
Bovine leptospirosis is an important disease that affects the reproductive sphere. Due to its high relevance for the bovine production chain in a worldwide scenario, a better understanding of the disease is crucial to reduce its negative impacts. The main agents are strains from the Sejroe serogroup, such as Hardjo and Guaricura, which lead to renal and genital infection. The genital colonization causes a chronic, silent, and subclinical reproductive syndrome, called Bovine Genital Leptospirosis (BGL). Embryonic death, estrus repetition, subfertility, and abortions are the main signs of BGL condition in females. However, although leptospires have been identified in semen, the manifestation of BGL in bulls remains to be clarified. The recommended diagnosis of BGL includes a serologic screening of the herds using the microscopic agglutination test followed by PCR of genital samples (cervicovaginal mucus, uterine fragment, or semen), especially from animals with reproductive failures. After the identification of carriers, control is carried out considering three steps: antimicrobial treatment of the carriers, environmental and reproductive management, and herd vaccination. Systematic testing, quarantine of newly arrived animals, and usage of antimicrobials in semen diluents or embryo culture media are other sanitary approaches that are encouraged to improve the control of the syndrome. Herein we discuss protocols for an efficient diagnosis and preventive procedures of BGL, which are fundamental to reducing the negative impact of the disease on cattle reproduction and its consequent economic hazards.